Content analysis of manuscript titles - Panjehpour, Panjehpour; Sorooshian, Shahryar (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The main objective of this write-up is to examine the class of manuscript titles of all publication of a case author. To accomplish the objective, the manuscript titles statements have been explored guiding through a study by Fox, Charles W., and C. Sean Burns. Quantity of characters and subtitles used in the manuscripts were considered. The conclusion point toward the capability of the case author’s works of being match with the Fox Charles and Sean Burns’s findings. Further studies may include more case analysis; this can be a practice to standardize the authors work.